2021
DOI: 10.36956/sms.v2i1.238
|View full text |Cite
|
Sign up to set email alerts
|

Oceans and COVID-19: Perspectives, Reflections, Recovery and Regulatory Frameworks

Abstract: The Novel Coronavirus outbreak that originated in Wuhan city of China in December 2019 assumed the global pandemic proportions during 2020. The disease it causes (termed as COVID-19) has created an unprecedented public health crisis, taken 1,324,461 lives so far, infected 54,817,231 people around the world, battered the global economy and paralyzed the normal activity. The world has been pushed into recession with resulting long-term financial hardship and social misery for all and global goals of development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The habitat mosaic that so develops supports marine biodiversity and abundance while prolonging the lifespan of the physical structures. The significance of three-dimensional artificial microhabitats for fish through experimental trials has been observed by Arsin et al (2018) and the need for living coastlines is discussed in a recent article (Mustafa et al, 2020). Quantitative data on how topographic complexity drives species diversity published recently (Bradford et al, 2020;Strain et al, 2020) provide support for the use of 3D-printed structures mounted on hard surfaces.…”
Section: Eco-engineering Solutions and The Living Coastlinementioning
confidence: 97%
See 1 more Smart Citation
“…The habitat mosaic that so develops supports marine biodiversity and abundance while prolonging the lifespan of the physical structures. The significance of three-dimensional artificial microhabitats for fish through experimental trials has been observed by Arsin et al (2018) and the need for living coastlines is discussed in a recent article (Mustafa et al, 2020). Quantitative data on how topographic complexity drives species diversity published recently (Bradford et al, 2020;Strain et al, 2020) provide support for the use of 3D-printed structures mounted on hard surfaces.…”
Section: Eco-engineering Solutions and The Living Coastlinementioning
confidence: 97%
“…Curtailing biodiversity loss and restoring ecosystem functions and services are among the key dimensions of the BBB approach. These are fundamental to the economy and human welfare (Mustafa et al, 2020;OECD, 2020). There are many challenges in understanding the true nature of marine biodiversity.…”
Section: Introductionmentioning
confidence: 99%